2016
DOI: 10.1097/qad.0000000000001155
|View full text |Cite
|
Sign up to set email alerts
|

Level of viral suppression and the cascade of HIV care in a South African semi-urban setting in 2012

Abstract: In Orange Farm, between 2005 and 2012, ART programs were suboptimal and, among those living with HIV, the proportion with viral suppression was still low, especially among the young age groups. However, our study showed that, in reality, antiretroviral drugs are highly effective in viral suppression at an individual level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
4
20
1
Order By: Relevance
“…Findings specifically support those of earlier studies that identified alcohol use as a risk factor for lower engagement in HIV care, 2123,27,60 treatment with ART 24,25,27 and viral suppression. 26,27 Moreover, this study newly demonstrated a dose-dependent association between alcohol use and three HIV care continuum outcomes such that PLWH reporting alcohol use at medium, high, and very high levels had progressively lower likelihood of all care continuum outcomes relative to patients who reported non-drinking.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings specifically support those of earlier studies that identified alcohol use as a risk factor for lower engagement in HIV care, 2123,27,60 treatment with ART 24,25,27 and viral suppression. 26,27 Moreover, this study newly demonstrated a dose-dependent association between alcohol use and three HIV care continuum outcomes such that PLWH reporting alcohol use at medium, high, and very high levels had progressively lower likelihood of all care continuum outcomes relative to patients who reported non-drinking.…”
Section: Discussionsupporting
confidence: 85%
“…In the U.S., 54% of PLWH report any alcohol use and 25% report any heavy episodic drinking, an unhealthy pattern of use known to adversely influence multiple health outcomes. 13 Alcohol use is associated with HIV care including: testing 1416 and diagnosis; 17 care engagement, 18 quality, 19 and retention; 2023 receipt and use of ART; 24,25 and potentially viral suppression. 2628 Thus, alcohol use may represent a modifiable influence on HIV care continuum targets.…”
Section: Introductionmentioning
confidence: 99%
“…Under the constant effort scenario we assume that 90% of people on ART are virally suppressed based on a study carried out in South Africa. 11 Under the expanded treatment and prevention scenario we assume that 96.5% of people on ART are virally suppressed based on a study carried out in Botswana. 12 We assume that the infectiousness of those that are not virally suppressed is 12% of the infectiousness of people that are not on ART (see Appendix 1).…”
Section: Data Sources and Assumptionsmentioning
confidence: 99%
“…Each of these proportions is multiplied by an overall rate at which people start treatment. We assume that 92% of people on ART are virally suppressed 11 and that the infectiousness of those that are not virally suppressed is 12% of the infectiousness of people that are not on ART (see Appendix 1). Rates are all per adult aged 15 years or more.…”
Section: Data Sources and Assumptionsmentioning
confidence: 99%
“…Meeting the '90-90-90' targets requires an approximate population viral suppression rate among all PLWH, including those not in care, of approximately 73%. Most of the published work evaluating the '90-90-90' targets have relied on special surveys [7][8][9][10] or mathematical models [11,12], and when routine data are used, the results typically provide only a snapshot of the progress for a 1-year period [13,14].…”
Section: Main Text Introductionmentioning
confidence: 99%